Employment concepts of college students in china and abroad: A systematic literature review - Zhang, Ziran; Hasan, Ahmad; Yue, You (Global Academic Excellence (GAE), 2024)
Chinese college students is quite prevalent. The academic community has previously conducted in-depth research on the employment concepts of college students. This paper examines studies conducted by Chinese and foreign scholars on the employment concepts of college students. The study is a preliminary exploration based on literature reviews, readings, surveys, and perspectives, utilizing library resources such as circulars, books, journals, and websites. The results of the preliminary survey indicate that basic theoretical research and assessment methods in China and abroad are relatively mature, yielding rich outcomes. However, there are still significant issues to be addressed. Through systematic review, this article identifies the following urgent research issues. Firstly, socialism with Chinese characteristics has entered a new era, presenting new requirements for college students. The new connotation of college students' employment views under these circumstances is still unknown. Secondly, the research object of scholars is more concentrated on the graduates, and few people pay attention to the employment view of current college students. Finally, scholars rarely focus on a specific discipline when studying the employment views of college students.